Pure akinesia with gait freezing: a clinicopathologic study - Elkouzi, Ahmad (J Clin Mov Disord, 2017)
BACKGROUND: Pure akinesia with gait freezing is a rare syndrome with few autopsied cases. Severe freezing of gait occurs in the absence of bradykinesia and rigidity. Most autopsies have revealed progressive supranuclear palsy. We report the clinical and postmortem findings of two patients with pure akinesia with gait freezing, provide video recordings of these patients, and review the literature describing similar cases. We also discuss bradykinesia, hypokinesia and akinesia in the context of this clinical syndrome. CASE PRESENTATION: Two patients with the syndrome of pure akinesia with gait freezing were examined by the same movement disorder specialist at least annually for 9 and 18 years. Both patients initially exhibited freezing, tachyphemia, micrographia and festination without bradykinesia and rigidity. Both autopsies revealed characteristic tau pathology of progressive supranuclear palsy, with nearly total neuronal loss and gliosis in the subthalamus and severe neuronal loss and gliosis in the globus pallidus and substantia nigra. Previously published postmortem studies revealed that most patients with this syndrome had progressive supranuclear palsy or pallidonigroluysian atrophy. CONCLUSIONS: Pallidonigroluysian degeneration produces freezing and festination in the absence of generalized slowing (bradykinesia). Freezing and festination are commonly regarded as features of akinesia. Akinesia literally means absence of movement, and akinesia is commonly viewed as an extreme of bradykinesia. The pure akinesia with gait freezing phenotype illustrates that bradykinesia and akinesia should be viewed as separate phenomena. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40734-017-0063-1) contains supplementary material, which is available to authorized users.